Haemodynamic Changes with Different Pressure Pneumoperitoneum in Patients Undergoing Laparoscopic Cholecystectomy - Sattar, Muhammad Mudassar; Amer Ud Din; Murtaza, Mudassar; Mian, Muhammad Amer; Khalid, Warda; Wajid, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Laparoscopic cholecystectomy commonly involves the creation of pneumoperitoneum using carbon dioxide (CO₂), which can significantly influence cardiovascular dynamics. Objective: To compare the mean hemodynamic changes associated with different pneumoperitoneum pressures in patients undergoing laparoscopic cholecystectomy. Methodology: This randomized controlled trial was conducted in the Department of Surgery at Central Park Teaching Hospital, Lahore, from December 16, 2023, to June 17, 2024. A total of 70 patients were enrolled and randomly allocated into two groups of 35 each. Group 1 underwent laparoscopic cholecystectomy with low-pressure pneumoperitoneum (8–10 mmHg), while Group 2 had standard-pressure pneumoperitoneum (11–13 mmHg). Results: At 60 minutes, the mean MAP in Group 1 (low pressure) was significantly lower at 85.14 ± 5.93 mmHg compared to 97.83 ± 9.38 mmHg in Group 2 (p < 0.001). The mean heart rate was also lower in Group 1 (98.97 ± 12.45 bpm) versus Group 2 (108.51 ± 11.71 bpm; p = 0.002). Similarly, oxygen saturation was higher in Group 1 (96.80 ± 1.41%) than in Group 2 (94.43 ± 1.70%; p < 0.001). These findings indicate more stable hemodynamic parameters in patients subjected to lower pneumoperitoneum pressures. Conclusion: Low-pressure pneumoperitoneum (8–10 mmHg) during laparoscopic cholecystectomy results in significantly more favorable hemodynamic outcomes compared to standard-pressure pneumoperitoneum (11–13 mmHg). These findings support the clinical benefit of using reduced pressure settings when feasible.